A Distributed Pseudo TDMA Protocol for Multi-Transmit-Receive Wireless Mesh Networks - Xu, Y.; Chin, K.; Soh, Sie Teng (2016)
This paper proposes a novel, iterative, distributed Medium Access Control (MAC) for Multi-Transmit-Receive (MTR) Wireless Mesh Networks (WMNs). The MAC called PCP- TDMA aims to construct the shortest possible schedule that allows nodes to transmit to or receive from all their neighbors simultaneously over the same frequency. Compared to the state- of-the-art, namely a centralized algorithm called ALGO-2, and two distributed approaches, namely JazzyMAC and ROMA, the results show that PCP-TDMA achieves similar performance to ALGO-2, and outperforms JazzyMAC and ROMA significantly. Specifically, in a fully connected network, the superframe pro- duced by PCP-TDMA is respectively only 1/3 and 1/2 the length of that generated by JazzyMAC and ROMA.